The complete human resources writing guide - Arthur, Diane (American Management Association, 1997)
Here, at last, is a writing manual especially for human resources (HR) professionals. It combines clear, complete, how-to-do-it guidelines on writing with more than 100 samples of typical HR documents. Busy HR professionals and managers will appreciate the logical, easy-to-follow format of this book. Diane Arthur, formerly a frontline HR practitioner and now an HR consultant and author, leads you step by step through the seven stages of writing. From outline through revision, you'll discover techniques that make the process easier and more effective. The emphasis is on objective, style, and tone, not merely the mechanics of grammar and punctuation. You'll learn to overcome "blank page syndrome" and sidestep classic writing pitfalls. In sum, you'll learn to write for results - an approach that makes every HR document achieve its purpose.